Analisis Kesehatan Mangrove di Probolinggo Menggunakan Data Sentinel-2A - Rizky Mauli Diyah; Bowo Eko Cahyono; Agung Tjahjo Nugroho (Natural B, Journal of Health and Environmental Sciences, 2019)
Probolinggo is one of the regencies which is directly adjacent to the Madura Strait and this area has a coastal area of around 71,893 Km. This long coastal area cause the area has high risk of coastal abrasion, so that monitoring of the condition of mangrove forests is needed to prevent the abrasion. In the coastal areas of probolinggo mangrove forests are used into purposes fields such as tourism, disaster prevention, education and conservation. To maximize the role of the mangrove forests, the analysis of mangrove health analysis in Probolinggo is very important to do. Because of the large research area, the utilization of remote sensing becomes an important alternative method. This study utilizes Sentinel-2A satellite imagery using the supervised classification method for area classification and the Normalized Different Vegetation Index method to classify mangrove health. Based on the results of the supervised classification analysis, the accuracy test using overall accuracy gives the accuracy result of 96.57% and from the mangrove health classification it is known that most of the mangroves in Probolinggo are in good health with a percentage of 75.75% of the total mangrove area i.e 367.04 hectares . Further research on the correlation of mangrove health to water quality is suggested to get more complex information about mangrove health.